ANALYSIS OF THE FACTORS CAUSING THE LOW THOUGHTS OF STUDENTS - Santoso, Ribut; Subando, Joko; Fatimah, Meti (Proceeding of International Conference of Islamic Education, 2023)
This study aims to determine the factors that cause a decline in student morals. This study used a qualitative research method with a descriptive approach. The subjects of this study were students of MI Muhammadiyah Derasan Andong Boyolali, while the informants included school principals and teachers and students of MI Muhammadiyah Derasan Andong Boyolali. The method of collecting data in this study is the method of observation or non-participant observation, interview method and documentation method. The process of data analysis begins by examining all data from interviews, observations and comments related to the analysis of the factors causing low student morals and is continued by conducting data reduction and verification to draw conclusions. Data validity checking technique with data triangulation technique. The results of this study indicate that the factors causing the low morals of students at MI Muhammadiyah Derasan Andong Boyolali are; One, there is influence from the family environment. Two, There is influence from the social environment. The efforts made by the teacher in forming student morals at MI Muhammadiyah Deresan Andong Boyolali include; habituation, by greeting others and shaking hands. Exemplary, by greeting hen entering the classroom, speaking politely while teaching and reciting prayers when starting to study and when finishing studying. Advice, the teacher always gives advice to always apply commendable morals.